Screening of Key Proteins Affecting Floral Initiation of Saffron Under Cold Stress Using iTRAQ-Based Proteomics - Chen, Jing; Zhou, Guifen; Dong, Yan; Qian, Xiaodong; Li, Jing; Xu, Xuting; Huang, Huilian; Xu, Limin; Li, Liqin (Frontiers in Plant Science, 2021)
Background Saffron crocus (Crocus sativus) is an expensive and valuable species that presents preventive and curative effects. This study aimed to screen the key proteins affecting the floral initiation of saffron under cold stress and thus increasing yield by regulating the temperature. Results Protein expression profiles in flowering and non-flowering saffron buds were established using isobaric tags for relative or absolute quantitation (iTRAQ). A total of 5,624 proteins were identified, and 201 differentially abundant protein species (DAPs) were further obtained between the flowering and non-flowering groups. The most important functions of the upregulated DAPs were “sucrose metabolic process,” “lipid transport,” “glutathione metabolic process,” and “gene silencing by RNA.” Downregulated DAPs were significantly enriched in “starch biosynthetic process” and several oxidative stress response pathways. Three new flower-related proteins, CsFLK, CseIF4a, and CsHUA1, were identified in this study. The following eight key genes were validated by real-time qPCR in flowering and non-flowering top buds from five different growth phases: floral induction- and floral organ development-related genes CsFLK, CseIF4A, CsHUA1, and CsGSTU7; sucrose synthase activity-related genes CsSUS1 and CsSUS2; and starch synthase activity-related genes CsGBSS1 and CsPU1. These findings demonstrate the important roles played by sucrose/starch biosynthesis pathways in floral development at the mRNA level. During normal floral organ development, the sucrose contents in the top buds of saffron increased, and the starch contents decreased. In contrast, non-flowering buds showed significantly decreased sucrose contents under cold stress and no significant changes in starch contents compared with those in the dormancy stage. Conclusion In this report, the protein profiles of saffron under cold stress and a normal environment were revealed for the first time by iTRAQ. A possible “reactive oxygen species–antioxidant system–starch/sugar interconversion flowering pathway” was established to explain the phenomenon that saffron does not bloom due to low temperature treatment.